Efektivitas Program Percepatan Penurunan Stunting Di UPTD Puskesmas Kilan Kecamatan Batang Cenaku Kabupaten Indragiri Hulu - Eka Nuryani; Dadang Mashur (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Stunting is a form of nutritional problem in the life cycle that is very important to be considered and addressed immediately, because stunting is a form of growth and development failure caused by chronic malnutrition and repeated infections that require immediate intervention or management. As an effort to accelerate the reduction of stunting in the UPTD Puskesmas Kilan work area, the Supplementary Feeding Program (PMT) was implemented. The purpose of this study was to determine the effectiveness of the stunting reduction acceleration program through the Supplementary Feeding Program (PMT) at UPTD Puskesmas Kilan, Batang Cenaku District, Indragiri Hulu Regency. The theory used in this research is Budiani's (2007) program effectiveness theory with 4 (four) indicators, namely the accuracy of the Program Targets, Program Socialization, Program Objectives, and Program Monitoring. The method used in this research is descriptive qualitative research method, with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the acceleration program to reduce stunting through Supplementary Feeding (PMT) at UPTD Puskesmas Kilan, Batang Cenaku District, Indragiri Hulu Regency has not been effective. There are several inhibiting factors faced, namely the lack of ability of the implementing officers in implementing the program, then the communication factor because the program conveyed to the community has not been able to increase public understanding of the program.